Manejo da irrigação e eficiência do uso da água no cultivo do pimentão com e sem sombreamento - Padron, Richard Alberto Rodriguez (2016)
Strategies for managing irrigation can lead to better outcomes, such as performance, quality fruit and efficient use of irrigation water. This study aimed to determine the effect of different supplemental irrigation depth and water use efficiency in bell pepper crop, cultivated in open-field and with 50% shading. The experimental was in a randomized block design with four replications, in factorial arrangement. Irrigation treatments were: application of 25, 50, 75 and 100% of evapotranspiration and the control treatment without irrigation. The experimental unit was composed of 2 lines of 5 m long, without embroidery plants. The hybrid used was Arcade, The seedlings were transplanted two months after germination, with a separation of 1 m between line and 0.4 m between plants, 16 November 2013 and 23 November 2014. The irrigation system drip, with spacing of 0.2 m and emitter flow rate of 0.8 L h-1. The frequency of irrigation was daily. The reference evapotranspiration by Penman-Monteith/FAO crop evapotranspiration and the method of dual crop coefficient was calculated. Soil parameters were determined is: chemical analysis, texture, bulk density, field capacity and infiltration rate. The soil water content monitoring was performed with a time domain reflectometer and neutron probe. The parameters evaluated were: yield, plant height, stem diameter, leaf area index, chlorophyll index, dry matter and plant root, number of fruit per plant, fruit dry matter, fruit diameter and length. Also, economic analysis on system with and without irrigation was performed. The highest yield was obtained without shade (35.1 t ha-1) with 75% of evapotranspiration and with shade (22.2 t ha-1) with 50% of evapotranspiration. The maximum technical efficiency was obtained with 69.4% and 54.5% evapotranspiration, with and without shade, respectively. With shade, saving of 15% less irrigation water was obtained. The applied irrigation depth ranged from 70.4 to 401.8 mm in the years of study. The efficient use of irrigation water without and with shade was 30 kg m-3 and 20 kg m-3, respectively. The crop coefficient was influenced by precipitation, especially during the initial phase of growth, the values were kcini= 0.71, kcmed= 1.17 and kcfinal= 0.92, higher than those recommended by FAO-56. The without shade treatments resulted in higher values in: growth rate of stem diameter, chlorophyll index, number of fruit per plant. Treatments shade resulted in higher values in: growth rate of plant height; leaf area index; number of leaf per plant; the total plant dry matter; diameter, length and weight of fruits. The lower profitability was without irrigation and higher with the irrigation depth of 75% of evapotranspiration, with internal rate of return of 29 and 84%, respectively. The excess water deficit affects the phenology, yield, plant growth and leaf area development.